(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
COVID-19 has mobilized various industries to digitize them, with the education sector not being the exception. In addition, the teaching staff was faced with the responsibility of continuing with the educational service in a virtual modality and many of them presented difficulties for the implementation of a non-face-to-face education system and to function in virtuality. In this context, the TEC project: technology for educators and the community is created as an ally for Peruvian teachers in strengthening their digital skills. This project has been successfully implemented in two versions in which around 140 teachers were accompanied. Currently, work is being done on adapting the project for educators in rural areas, aware of the diversity of contexts in Peru and the need for an equitable and quality education in our country.